Digital Economy to Growing Up Communal Brand in Dawuhan Mangli Jember - Zulianto, Mukhamad; Setiawan, Rendy; Ramadhanti, Anisa; Anindya, Dinda Karina (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1150, 2020)
The era of the industrial revolution 4.0 made the internet an inevitable matter. The changes brought by the internet are an interesting discussion as to whether these changes are able to grow the economy for MSMEs. The digital economy is one of the efforts to develop a communal brand in the village of Dawaw Mangli Jember. The efforts of MSMEs in dawuhanmangli village as a birdhouse center also seem to have contributed to the development of the current digital economy. MSMEs in dawuhanmangli also market their products through marketplaces, social media, and other online optimizations.